2004
DOI: 10.1111/j.1365-2095.2003.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamins, minerals and lipid levels in diets for Atlantic salmon (Salmo salar, L.): effects on growth performance and fillet quality

Abstract: An experiment with 2(7 − 3) reduced factorial design was conducted to study the biological effects of pro‐ and antioxidant micronutrients and lipid in Atlantic salmon. Vitamins C and E, astaxanthin, lipid, iron, copper and manganese were supplemented at high and low levels. For vitamins and minerals, high levels were chosen to be below the anticipated toxic level and the low levels were just above the requirement (vitamin C, 30 and 1000 mg kg−1; vitamin E, 70 and 430 mg kg−1; Fe, 70 and 1200 mg kg−1; Cu, 8 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 59 publications
6
44
0
5
Order By: Relevance
“…Di antara vitamin tersebut, vitamin C yang terbanyak diaplikasikan oleh usaha budidaya tambak udang vaname yaitu 12 usaha budidaya tambak (41,38%). Vitamin C dan E, asam lemak esensial dan karotenoid telah dilaporkan dapat mengurangi dampak negatif dari tekanan lingkungan terhadap kesehatan organisme akuatik, meningkatkan ketahanan terhadap penyakit, dan juga secara umum meningkatkan kualitas produk akuatik (Cat acut an & Lav i lla-Pit ogo, 1 994; Boonyaratpalin, 2000;Hamre et al, 2004). Penggunaan vitamin C dengan dosis 150-500 mg/kg pakan komersial diaplikasikan pada tambak udang windu di Jawa Timur dengan hasil yang menggembirakan (Supriyadi & Rukyani, 2000 Rasio konversi pakan antara sistem budidaya udang intensif berbeda tidak nyata dengan sistem super-intensif di tambak Kabupaten Pesawaran (Tabel 6).…”
Section: Tambahan Pakanunclassified
“…Di antara vitamin tersebut, vitamin C yang terbanyak diaplikasikan oleh usaha budidaya tambak udang vaname yaitu 12 usaha budidaya tambak (41,38%). Vitamin C dan E, asam lemak esensial dan karotenoid telah dilaporkan dapat mengurangi dampak negatif dari tekanan lingkungan terhadap kesehatan organisme akuatik, meningkatkan ketahanan terhadap penyakit, dan juga secara umum meningkatkan kualitas produk akuatik (Cat acut an & Lav i lla-Pit ogo, 1 994; Boonyaratpalin, 2000;Hamre et al, 2004). Penggunaan vitamin C dengan dosis 150-500 mg/kg pakan komersial diaplikasikan pada tambak udang windu di Jawa Timur dengan hasil yang menggembirakan (Supriyadi & Rukyani, 2000 Rasio konversi pakan antara sistem budidaya udang intensif berbeda tidak nyata dengan sistem super-intensif di tambak Kabupaten Pesawaran (Tabel 6).…”
Section: Tambahan Pakanunclassified
“…Studies on vitamin E supplementation in diets for fish revealed its antioxidant action in in vivo and in the reduction of oxidation after death, with an improvement in conservation during storage (Onibi et al, 1996;Pirini et al 2000;Shiau and Shiau, 2001;Ruff et al, 2002;Hamre et al, 2004;Fogaça and Santana, 2007).…”
Section: Inmentioning
confidence: 99%
“…Os antioxidantes exógenos ou provenientes da nutrição (vitaminas C, E e os carotenóides) e seus cofatores (cobre, manganês, zinco, selênio, ferro e a riboflavina), também mantêm equilíbrio na produção e controle das espécies reativas (Papas, 1999;Hamre et al, 2004). A sua ingestão pode ser um fator pré-abate importante na preservação da qualidade FOGAÇA e SANT'ANA, 2009 ________________________________________________________________________…”
Section: Defesas Antioxidantes Em Peixesunclassified
“…Dessa forma, diversos trabalhos foram realizados com a suplementação de diferentes níveis de vitamina E em dietas para salmões do atlântico (Onibi et al, 1996;Hamre et al, 2004), robalos (Pirini et al, 2000;Gatta et al, 2000), pacus (Sant'Ana, 1998; Sant'Ana e Fernandes, 2000) e pregados (Ruff et al, 2002b;2003), sendo que todos descreveram redução nas taxas de oxidação e melhor conservação desses peixes durante a estocagem.…”
Section: Efeito Pró-oxidante Da Vitamina Eunclassified